Cognitive polyphasia and the iconic structure of the social representation of death / Polifasia cognitiva e a estrutura icônica da representação social da morte - Alexsandro Medeiros do Nascimento; Antonio Roazzi (Psicologia: Reflexão e Crítica, 2008)
The present study investigated the image structure of the social representation of death in healthcare professionals. A questionnaire with both open and closed-end questions was used to assess the symbolic and iconic components of the representation of death in a group of 49 physicians, 13 psychologists, and 18 nurses (54 female and 26 male). The data produced was analyzed through a non-metric multidimensional procedure - the SSA - and an "external variables as points" method. Finally, it was compared with the symbolism of death explored in previous studies (Nascimento, 2001b; Nascimento & Roazzi, 2007) and interpreted in the light of the theory of social representations and facet theory. Consistent indications of difficulties in the represen-tation of death and failures in the production of consensus were found, as well as a logical organization of imagistic elements which point out for a state of cognitive polyphasia in the representation of this object.